A Recombination-Based Internationalization Model: Evidence from Narayana Health’s Journey from India to the Cayman Islands - Gupta, Budhaditya; Khanna, Tarun (Organization Science, 2019)
Internationalizing firms often find developing host-country resources challenging as they simultaneously attempt to replicate the resources that worked well in the home country and adapt them to fit the context of the host country. On the basis of a longitudinal study of the expansion of India-domiciled Narayana Health (NH), a tertiary healthcare provider, to the contextually distinct Cayman Islands, we propose a recombination-based internationalization model that allows us to offer a new conception of this replication–adaptation tradeoff. Recombination entails creating anew in the host country by drawing from, adapting, and integrating diverse resources developed earlier in heterogeneous settings in the home country. We theoretically explore the mechanisms underlying such recombination processes in organizational settings.